Failure of femoral neck fracture fixation in younger patients - Soeharno, Henry; Silva, Amila Nirmal; Tay, Adriel; Koon, Wong Merng (International Journal of Research in Orthopaedics, 2019)
Background: Failure of femoral neck fracture fixation in younger patients frequently lead to significant morbidity. This study aims to evaluate the associated risk factors, to help achieve better outcomes. Methods: Records of 25 men and 6 women aged 23 to 50 (mean, 39.8) years who underwent fixation for femoral neck fractures using cancellous screws (n=29), a dynamic hip screw (n=1), or a locking plate (n=1) were reviewed. Patients with or without fixation failure were compared. Results: The mean follow-up period was 28.4 (range, 24–38) months. Of the 31 patients, 24 had bone union and 7 had fixation failure secondary to non-union (n=1), screw cut-out (n=4), and avascular necrosis (n=2). The Revised Trauma Score on admission was 4 in one patient with fixation failure and >6 in all other patients. Comparing patients with or without fixation failure, excess alcohol consumption (5/7 vs. 6/24, p=0.024), smoking (6/7 vs. 9/24, p=0.025), and operative time in minutes (57±16 vs 108±58, p=0.00004), fracture type of OTA 31 B2 or 31 B3 (7/7 vs. 14/24, p=0.027) were significant risk factors. Conclusions: Excess alcohol consumption, smoking, operative time >85 minutes, and displaced fractures were risk factors for femoral neck fixation failure.